2021
DOI: 10.3390/ijerph182312528
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Literacy in Individuals with Chronic Pain and Its Association with Psychological Function

Abstract: Electronic health literacy skills and competences are important for empowering people to have an active role in making appropriate health care decisions. The aims of this cross-sectional study were to (1) examine the frequency of use of the Internet for seeking online information about chronic pain, (2) determine the level of eHealth literacy skills in the study sample, (3) identify the factors most closely associated with higher levels of eHealth literacy, and (4) examine self-efficacy as a potential mediator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 63 publications
2
14
0
1
Order By: Relevance
“…Most of participants (94%, n=184) had high eHealth literacy with an eHEALS score of 26 or higher, which is consistent with previous studies with individuals facing chronic pain (Castarlenas et al, 2021) or other chronic conditions (Richtering et al, 2017). This is also consistent with participants being recruited online, thus most likely to be using internet resources.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Most of participants (94%, n=184) had high eHealth literacy with an eHEALS score of 26 or higher, which is consistent with previous studies with individuals facing chronic pain (Castarlenas et al, 2021) or other chronic conditions (Richtering et al, 2017). This is also consistent with participants being recruited online, thus most likely to be using internet resources.…”
Section: Discussionsupporting
confidence: 86%
“…For instance, being married and having less education can lead to reliance on family members as opposed to developing self-efficacy skills and potentially eHealth literacy. Nonetheless, regarding age more specifically, Castarlenas et al (Castarlenas et al, 2021) did not find that the level of eHealth literacy was associated with age in chronic pain patients. Indeed, another study with a cardiovascular population observed that this relationship seems to disappear when included in a logistic regression model to let "time spent on the internet" prevail (Richtering et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The cross-sectional survey study “Electronic Health Literacy in Individuals with Chronic Pain and its Association with Psychological Function” by Castarlenas et al [ 11 ] examines the association between electronic health literacy (eHealth literacy) and health-related behaviours in people with chronic pain, not least because people with chronic illnesses make more frequent use of and rely on health information and services more than individuals without such conditions. According to the authors, the “good news” for clinical implications is that eHealth literacy can be learned, which is important for (electronic) health literacy development given the challenges that people have in finding good quality health information in the seemingly endless online information landscape.…”
Section: Articles In the Special Issuementioning
confidence: 99%